An Error Analysis of Communicative Effect Taxonomy of The Tenth Grade Students’ Writing of Descriptive Text - Yaredi Waruwu,; Afore Tahir Harefa, (RETORIKA: Jurnal Ilmu Bahasa, 2024)
The purpose of this research analyzes the errors that students in the tenth grade experienced when writing descriptive texts for the communicative effect taxonomy. The findings indicated the students made both global and local errors in communicative effect taxonomy. The most frequently local errors produced by the students which consist of 44 or 57, 14%, that consist of 4 kinds; noun and verb with total error 28 or 36, 36%, article with the total error 14 or 18, 18%, quantifier with the total error 1 or 1, 29% and auxiliary with the total error 1 or 1, 29%., followed by global error with the total error 33 or 42, 85 error. Intralingual was the highest frequentcy of the students, response with the frequency of source was 26 or 31,70%, interlingual was 24 or 29,26%, context of learning was 24 or 29,26% and communication strategy was 8 or 9,75%.